THE INFLUENCE OF TRUST, COMMITMENT, COMMUNICATION, AND HANDLING OF COMPLAINTS TOWARD CUSTOMER LOYALTY AT OTOMOTO MANADO - Supit, Juan Soleman; Mandey, Silvya L.; Moniharapon, Silcyljeova (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Customer loyalty is one of the most important variables for the success of a company because customer loyalty positively affects company profits through cost reduction effects and the addition of income. Loyalty will provide many advantages for companies, including retention and recommendations regarding the purchase of the brand to friends and acquaintances. This is what underlies the enthusiasm of the business on customer loyalty. This study aims to determine the effect of the dimensions of trust, commitment, communication, and handling of complaints toward customer loyalty at Otomoto Manado. The analytical method used is associative with the Multiple Linear Regression Analysis as well as the Test of Classical Assumption. The population in this study is the customers of Otomoto and who have experienced service or purchased as much as two times, which amounts to 276 customers and a sample of 75 respondents were chosen. The results of the simultaneous analysis of trust, commitment, communication, and handling of complaints variables have effect on customer loyalty. Partially, trust, commitment, and the handling of complaints have positive effect on customer loyalty, and communication does not have positive effect on customer loyalty. The Otomoto Manado management needs to improve further customer loyalty in order to improve their competitiveness with other competitors. Keywords: trust, commitment, communication, handling of complaints, customer loyalty